2022
DOI: 10.1021/acs.jpcb.2c05674
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Structure of Na+ and K+ Ions in Solution Predicted by Data-Driven Many-Body Potentials

Abstract: The hydration structure of Na + and K + ions in solution is systematically investigated using a hierarchy of molecular models that progressively include more accurate representations of many-body interactions. We found that a conventional empirical pairwise additive force field that is commonly used in biomolecular simulations is unable to reproduce the extended X-ray absorption fine structure (EXAFS) spectra for both ions. In contrast, progressive inclusion of many-body effects rigorously derived from the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 135 publications
4
32
0
Order By: Relevance
“…This difference motivates our focus on the 20 K spectra. The coordination number ( N ) of hydrated K + is consistent with 6 ± 2 oxygen atoms (from water molecules or O‐atoms within CoCat) surrounding the K + ion; [ 57 ] a coordination number close to 7 seems likely [ 58,59 ] ( Figure , motif δ ). In our EXAFS simulations, the longer distances relating to peaks II and III in the FT‐spectrum are modeled as a KOPO 3 motif (peak II, KP around 3.5 Å, motif γ in Figure 4) and a KOCo motif (peak III, KCo around 4.1 Å, motif β in Figure 4).…”
Section: Resultsmentioning
confidence: 69%
“…This difference motivates our focus on the 20 K spectra. The coordination number ( N ) of hydrated K + is consistent with 6 ± 2 oxygen atoms (from water molecules or O‐atoms within CoCat) surrounding the K + ion; [ 57 ] a coordination number close to 7 seems likely [ 58,59 ] ( Figure , motif δ ). In our EXAFS simulations, the longer distances relating to peaks II and III in the FT‐spectrum are modeled as a KOPO 3 motif (peak II, KP around 3.5 Å, motif γ in Figure 4) and a KOCo motif (peak III, KCo around 4.1 Å, motif β in Figure 4).…”
Section: Resultsmentioning
confidence: 69%
“…The differences between the EPSR-based and MB-nrg RDFs may be due to various reasons, including inaccuracies of the MB-nrg PEF which may be related to intrinsic inaccuracies of the DF-MP2/AVQZ training data and/or inaccuracies in the description of NMA–H 2 O n -body energies with n > 2 which are only represented by many-body polarization in the current MB-nrg PEF. In this regard, it was shown explicitly representing 3-body energies with a 3-body PIP, in some cases, slightly improves the agreement with experimental measurements of extended X-ray absorption fine structure (EXAFS) spectra. ,,, Another possible reason for the differences between the EPSR-based and MB-nrg RDFs may be related to the higher NMA concentration used in the experiments. In this regard, from the analyses of the NDIS measurements reported in ref , it was concluded that, at the concentration used in the experiments, NMA molecules can form hydrogen-bonded dimers and possibly chains.…”
Section: Resultsmentioning
confidence: 82%
“…The many-body expansion (MBE) of the energy allows for rigorously expressing the total energy of an N -body system as a sum of n -body energy contributions (1 ≤ n ≤ N ) according to Here, the 1-body energy, ε 1B ( i ), refers to the distortion energy of the i th monomer relative to its minimum-energy geometry, i.e., ε 1B ( i ) = E ( i ) – E eq ( i ), where E ( i ) and E eq ( i ) are the energies for the distorted and equilibrium geometries, respectively. For n ≥ 2, the n -body ( n B) energies are defined recursively through the following expression: Since the MBE converges quickly for nonmetallic systems, eq provides a rigorous and efficient theoretical/computational framework for the development of full-dimensional PEFs where each n -body energy term is fitted to reproduce the corresponding reference values obtained from electronic structure calculations (see refs , , , , , , , , and ). Examples of many-body PEFs derived from eq are the Thole-type-model energy (TTM-nrg) , and many-body energy (MB-nrg) , PEFs for generic solutes in water.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that MB-pol also represented the first step toward the development of the many-body energy (MB-nrg) theoretical/computational framework, which exploits the “nearsightedness” of electronic matter to rigorously represent the energy of a given molecular system in terms of individual many-body contributions . In this context, MB-pol was used to represent water in MB-nrg PEFs of various aqueous systems, including halide and alkali-metal ions in water, , CH 4 /H 2 O mixtures, , and CO 2 /H 2 O mixtures. , In particular, MB-nrg PEFs developed for alkali-metal and halide ions were shown to accurately predict the structures, binding and interaction energies, and vibrational spectra of small X – (H 2 O) N (with X = F, Cl, Br, and I) and M + (H 2 O) N (with M = Li, Na, K, Rb, and Cs) clusters as well as the hydration structures of Cl – , Br – , I – , Na + , K + , and Cs + in solution. …”
Section: Introductionmentioning
confidence: 99%